Finding Common Ground - Jeffs, Tony (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2014)
This text focuses on the development of informal education and its relationship with parallel traditions notably youth work, adult education, informal learning and social pedagogy. Some discussion will occur regarding the tensions between formal and informal education. Finally consideration will be given to the recent and contemporary role of the state in relation to the funding and development of informal education.